การจัดกิจกรรมโดยใช้แนวความคิดการรับรู้ความสามารถของตนเองเพื่อเสริมสร้างความพร้อมในการเรียนรู้ด้วยการนำตนเอง - วงษ์ประคอง ปภาพัศร์; ไสยโสภณ ปิยะพงษ์; วัฒนะ จุฬารัตน์ (KASEM BUNDIT JOURNAL, 2021)
PURPOSES: To develop and to evaluate the results of the use of the learning activity to enhance self-directed learning readiness of teachers at Sriracha Vocational College, Chon Buri province. METHODS: One group pretest-posttest experimental design was employed in this research. The group comprised 30 teachers at Sriracha Vocational College, Chon Buri province who voluntarily participated in this study. The instruments used for collecting data were a measurement test of self-directed learning readiness scale (SDLRS) and a satisfaction questionnaire survey form. RESULTS: Learning activity on self-efficacy concept for enhancing self-directed learning readiness of teachers was developed through integration among self-efficacy concept and self–directed learning readiness which consisted of 8 activities i.e. opening the world of learning, looking yourself, steps for learning, goal setting, loving to learn, creative thinking, positive power, and empowerment of learning. The result of the use of the developed learning activity after training level in terms of self-directed learning readiness (SDLR) was higher (m=4.52) (s=0.253) than the pre training (m=3.57) (s=0.309). In addition, the teachers were satisfied with the learning activity based on self-efficacy concept at the excellent level (m=4.70) (s=0.466) CONCLUSION: The developed learning activity could enhance self-directed learning readiness of teachers in all eight aspects.